Health Literacy and Intercultural Competence Training - Michelle Mavreles Ogrodnick; Mary Helen O'Connor; Iris Feinberg (SLACK Incorporated, 2021)
Intercultural competence (ICC) and health literacy (HL) are vital components of patient education. The purpose of this study was to determine if an educational intervention that combined ICC and HL was effective at changing second-year nursing students' self-efficacy, beliefs, and knowledge. A total of 157 second-year nursing students in two different programs participated in pre- and post-surveys consisting of the Transcultural Self-Efficacy Tool and Health Literacy Beliefs and Knowledge survey. Students attended a two-part lecture with a moderated panel on ICC and health literacy and began clinical fieldwork. Results were analyzed using Wilcoxon signed-rank test and Pearson correlation. There was a statistically significant difference in all ICC subscales after an educational intervention and clinical fieldwork (cognitive z = 7.681, p < .001; practical z = 7.319, p < .001; affective z = 6.533, p < .001). HL knowledge and belief measures showed statistically significant difference after the intervention (z = 3.037, p < .001). There was a statistically significant correlation between intercultural self-efficacy and HL beliefs (Pearson's r = .486, p < .001). Self-efficacy in ICC and beliefs and knowledge in HL increased over time for nursing students, indicating that it may be beneficial to train students about these two constructs simultaneously. [HLRP: Health Literacy Research and Practice. 2021;5(4):e283-e286.]